PENENTUAN NILAI EVAPOTRANSPIRASI DAN KOEFISIEN TANAMAN BEBERAPA VARIETAS PADI UNGGUL DI RUMAH KACA FAKULTAS PERTANIAN UNIVERSITAS SUMATERA UTARA (Determination of Value of Evapotranspiration And Plant Coefficient of Some Rice of Varieties In the Faculty - Indi Sajiwo; Sumono Sumono; Lukman Adlin Harahap (Universitas Sumatera Utara, 2017)
ABSTRACT The water requirement of rice crop include saturation, percolation, flooding and evapotranspiration. The amount ofevapotranspiration can be determined based on the value of potensial evaporation and the rice crop coefficient values for each period of growth. This study was aimed to assess the value of evapotranspiration and crop coefficient of Situ Bagendit, Ciherang and Makongga Varieties In Green house of Faculty of Agriculture, University of North Sumatra.The results showed that the value of the evapotranspiration of rice plants at Situ Bagendit, Ciherang and Makongga varieties were the vegetative phase of 1,68 mm/day, 1,68 mm/day and 1,69 mm/day respectively, at the reproductive phase were 1,83 mm/day, 1,72 mm/day and 1,76 mm/day respectively and the phase of ripening were 1,71 mm/day, 1,69 mm/day and 1,70 mm/day respectively. The plant coefficient ofSitu Bagendit, Ciherang and Makongga varieties at the vegetative phase were 1,20 mm/day,1,20 mm/day and 1,21 mm/day respectively, at the reproductive phase were 1,14 mm/day, 1,07 mm/day and 1,08 mm/day respectively and at the phase of ripening were 1,05 mm/day, 1,03 mm/day and 1,05 mm/day respectively. Ciherang variety had a value of grain production higher compared to Situ Bagendit and Makongga. The productivity ofrice of Situ Bagendit was 102,81 gram, Ciherang was 124,16 gram and Makongga was 94,48 gram respectively. Keywords: Evapotranspiration, Plant coefficient, Rice, High Yield Variety, greenhouse. ABSTRAK Kebutuhan air areal tanaman padi meliputi penjenuhan, perkolasi, penggenangan dan evapotranspirasi. Besarnya nilai evapotranspirasi dapat ditentukan berdasarkan nilai evaporasi potensial dan nilai koefisien tanaman padi untuk setiap periode pertumbuhannya. Penelitian ini bertujuan untuk menentukan Evapotranspirasi dan Nilai Koefisien Tanaman Padi Situ Bagendit, Ciherang dan Makongga Di Rumah Kaca Fakultas Pertanian Universitas Sumatera Utara. Hasil penelitian menunjukkan besar nilai Evapotranspirasi tanaman padi pada varietas Situ Bagendit, Ciherang dan Makongga yaitu pada fase vegetatif 1,68 mm/hari, 1,68 mm/hari dan 1,69 mm/hari, fase reproduktif 1,83 mm/hari, 1,72 mm/hari dan 1,76 mm/hari, fase pemasakan 1,71 mm/hari, 1,69 mm/hari dan 1,70 mm/hari. Nilai koefisien tanaman padi pada varietas Situ Bagendit, Ciherang dan Makongga yaitu pada fase vegetatif 1,20 mm/hari, 1,20 mm/hari dan 1,21 mm/hari, fase reproduktif 1,14 mm/hari, 1,07 mm/hari dan 1,08 mm/hari, fase pemasakan 1,05 mm/hari, 1,03 mm/hari dan 1,05 mm/hari. Varietas Ciherang memiliki nilai produksi bulir padi yang lebih tinggi dibandingkan dengan varietas Situ Bagendit dan Makongga. Produktivitas bulir padi untuk varietas Situ Bagendit 102,81 g, varietas Ciherang 125,16 g dan varietas Makongga 94,48 g. Kata kunci : Evapotranspirasi, Koefisien Tanaman, Tanaman Padi, Varietas Unggul, Rumah Kaca.